TINJAUAN HUKUM KEDUDUKAN AHLI WARIS DALAM HAK PAKAI TANAH DI LINGKUNGAN BENTENG KERATON BUTON KELURAHAN MELAI - Wa Ode Zamrud; Muhammad Syarifuddin; Nur Sadila Sari Mimu (Jurnal Ilmu Hukum Kanturuna Wolio, 2022)
Legal review of the heirs' position in the right to use land in the Buton Fort Palace, Melai Village. The problems of this research are: (1) How. remedies for use by the heirs so that the usufruct rights acquired by him still have legal force in the buton palace fort, melai village (2) Restrictions - what are the obstacles for the heirs in the land use rights in the buton palace fort, melai village empirical legal law . Data sources consist of secondary data and primary data collected through interviews and documentation. The results of the collected data were then analyzed qualitatively. The results of this study indicate: (1) the legal efforts of the heirs so that the obtained usufruct rights still have legal force in the Buton Palace fort, melai village, including the implementation of the usufruct rights, the legal status of the building, the mechanism in the implementation of the land use rights agreement (2) What are the barriers for the heirs in the use of land rights in the Buton Palace Fort, Melai Village to get clarity on the results of the implementation of the land use rights.